Anti-KL-6/MUC1 monoclonal antibody reverses resistance to trastuzumab-mediated antibody-dependent cell-mediated cytotoxicity by capping MUC1. (1st February 2019) - Namba, Masashi; Hattori, Noboru; Hamada, Hironobu; Yamaguchi, Kakuhiro; Okamoto, Yohei; Nakashima, Taku; Masuda, Takeshi; Sakamoto, Shinjiro; Horimasu, Yasushi; Miyamoto, Shintaro; Iwamoto, Hiroshi; Fujitaka, Kazunori; et al.
Abstract: Polymorphic epithelial mucin (MUC1) is generally overexpressed on the surface of most adenocarcinomas including breast cancer. MUC1 is associated with chemotherapeutic resistance and immune evasion of cancer cells; however, the association between MUC1 and trastuzumab-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) remains unclear. In this study, using six breast cancer cell lines with differing expression levels and MUC1 distribution, the present results show that cells with MUC1 overexpression and uniform surface distribution were resistant to trastuzumab-mediated ADCC. Importantly, trastuzumab resistance was reversed upon siRNA-mediated MUC1 knockdown and by using anti-KL-6/MUC1 monoclonal antibody (mAb). Additionally, we visually confirmed that anti-KL-6/MUC1 mAb induced capping of MUC1 molecules on the cell surface, resulting the in death of these cells. These results suggest that not only the quantity but also the cell-surface distribution of MUC1 affects the sensitivity of breast cancer cells to trastuzumab-mediated ADCC. Highlights: Even MUC1 membrane distribution helps acquire resistance to trastuzumab-mediated ADCC. siRNA-mediated MUC1 knockdown reverses resistance to trastuzumab-mediated ADCC. MUC1 capping by anti-KL-6/MUC1 mAb makes ADCC-resistant cancer cells susceptible.